Benchmark analysis of electricity consumption for complex campus buildings in China. (25th February 2018) - Ding, Yan; Zhang, Zhenqin; Zhang, Qiang; Lv, Wenhui; Yang, Zhichao; Zhu, Neng
Highlights: Subentry electricity consumption is considered for campus building benchmarks. New methods of electricity benchmarking for complex campus buildings are proposed. A rating system is established based on new benchmarks. Abstract: Publicising the energy consumption of buildings is an effective way to promote building energy efficiency in colleges and universities. The aim of this study is to propose a method for developing electricity benchmarks for complex campus buildings. This study uses various statistical methods to determine such benchmarks. The determination of new electricity benchmarks includes the following steps: (a) determination of the factors influencing electricity consumption, (b) standardisation of indicators, and (c) calculation and correction of the electricity benchmarks. Thirteen complex buildings from the hot summer and cold winter zone of China were selected as samples to illustrate the standardisation process. The total electricity and subentry electricity benchmarks are determined based on multiple linear regression analyses. Multi-factor analyses of variance were used to identify the categorical factors that have significant influences on electricity consumption and on the correction of benchmarks. Finally, a rating system for the evaluation of electricity consumption was also established that applied the corrected electricity benchmarks.